A microplasticity evaluation method in very high cycle fatigue. (January 2017) - Wang, X.G.; Feng, E.S.; Jiang, C.
Highlights: A full-field calorimetric method is applied to ultrasonic fatigue testing. An energy analysis method is proposed for the microplastic strain evaluation. The Manson-Coffin law is established in the very high cycle fatigue regime. The strain-dependent fatigue mechanism of polycrystalline copper is revealed. Abstract: This paper is concerned with an application of full-field calorimetric method for the microplasticity evaluation in the very high cycle fatigue regime. The employed method is essentially based on the establishment of an experimental energy balance during the fatigue process. It allows the estimation of the plastic strain of very low magnitude produced by cyclic slip, which is considered as the primary mechanism of the ultrahigh cycle fatigue in the face-centered cubic materials. By the developed method, the plastic strain amplitudes of a polycrystalline copper in the very high cycle fatigue regime are estimated, and its relationship with the fatigue lives is established via the Manson-Coffin law.